Study of socio-demographic factors and comorbidities in children with attention deficit hyperactivity disorder admitted in a tertiary care centre - M., Sindhuprasath; Sucindar M.; Ramamoorthy R.; Chidambaranathan S. (International Journal of Contemporary Pediatrics, 2023)
Background: Objectives of the study were to study the socio-demographic factors and co-morbidities in Indian children with attention-deficit/hyperactivity disorder (ADHD). Methods: A prospective observational study of 2 years duration at the pediatrics department, Rural tertiary care center in Tamil Nadu, using diagnostic and statistical manual 5 (DSM-5) criteria-based questionnaires. Results: 60 children met the diagnosis of ADHD. M: F ratio was 3.6:1. The mean age was 8.2 years. A majority of the children belonged to lower socio-economic classes and were first-born children. Most children were brought up in nuclear families. A history of delayed speech and language development was commonly seen in these children. The combined type of ADHD was the most common. At least two co-morbid diagnoses were seen in most of the children, and anxiety disorder was the most common co-morbid diagnosis. Conclusions: Knowledge about their sociodemographic profile and other co-morbid conditions that are associated with ADHD is necessary to the fully understand the magnitude of the problem and to the plan effective therapy for them.